AB0850 Do symptoms of depression and anxiety influence treatment response and long-term physical health outcomes in ankylosing spondylitis?. (12th June 2018) - Eusébio, M.; Lopes, C.A.; Bernardes, M.; Pinto, P.; Santos, H.; Gomes, J.L.; Tavares-Costa, J.; Dias, J.; Bernardo, A.; Domingues, L.; Crespo, C.; Maia, S.; et al.
Abstract : Background: Psychological disturbances, frequently observed in inflammatory rheumatic diseases, seem to negatively influence patient's clinical status and treatment response. Objectives: The aim of this study was to examine the longitudinal impact of depression (D)/anxiety (A) in treatment response, disease activity, physical disability and quality of life in patients with Ankylosing Spondylitis (AS). Methods: Data from patients who fulfilled the modified New York criteria for AS were collected at baseline, weeks 2 and 14 post-treatment with Adalimumab. The Hospital Anxiety and Depression Scale (HADS) was used to evaluate D/A symptoms severity. The primary outcomes were AS disease activity score – C reactive protein (ASDAS-CRP), Bath AS Disease Activity Index (BASDAI), Bath AS Functional Index (BASFI) and AS Quality of Life (ASQoL) Scale. Secondary outcomes were patient and physician global assessment by Visual Analogue Scale (VAS), erythrocyte sedimentation rate (ESR), CRP and BASDAI question 1 (fatigue). Difference-in-differences estimation took into account the covariates gender, age at baseline and disease duration. Results: Data from 54 patients were included. At baseline, D/A symptoms significantly influenced the mean value of BASFI (p=0.006; p=0.003) and ASQoL (p<0.001; p=0.004). On the other hand, BASDAI (p=0.009), CRP (p=0.017), patient's VAS (p=0.003) and fatigue (p=0.015) were only influenced in the individuals with A symptoms, while the physician's VAS (p=0.005) was only influenced in patients with D symptoms. After 14 weeks of treatment, significant differences in ASQoL mean values were found in patients with both D/A symptoms at baseline (p=0.005; p=0.022) and in BASFI (p=0.044) and patient VAS (p=0.006) for the population showing only A symptoms at the baseline. Apart from the physician VAS (p=0.023), D/A baseline symptoms did not affect the treatment's response. Conclusions: Psychological status does not seem to affect response to treatment with Adalimumab, even if the overall characteristics of the population are different at baseline between patients with/without D/A symptoms. Disclosure of Interest: None declared